The Impact of Food Operational Control Cycle Towards Food Cost Management: a Comparison Study of 3 Branches of Korbeq Restaurant by Stevan Meatshop - Jason Liuden; Rano Abryanto (Conference Series, 2020)
This research aims to investigate the impact of food operational control cycle towards restaurant food cost management in Korbeq restaurant by Stevan Meat Shop. In this research it will mainly focus on quantitative methods however to strengthen the study it will also be supported with qualitative methods and direct observation before the pandemic occurs. Furthermore, this study has come up with the conclusion that the food operational control cycle has an impact on food cost management. Based on results it shows that food operational control cycle contributes 41.9% on impacting food cost management on restaurant operations, and another 58.1% was caused by other factors that are not mentioned in this study. The dimensions of food operational control cycle also analyzed using descriptive study supported with qualitative data to determine which factors of food operational control cycle has the most impact. As a result, issuing and production are determined as the most impactful dimension. The other dimension of the food operational control cycle are menu planning, purchasing, receiving, storing, service. This research was analyzed through IBM SPSS ver 25.